(untitled) (Journal of the Sociology and Theory of Religion, 2025)
The germ of economic development is human action, which crystallizes in the business function. The will to prosper of the individual is what makes the whole of society prosper, through voluntary social coordination between individuals. In this paper we focus on the cognitive traits that give rise to human action. In particular, we postulate the importance that religiosity, human values and a positive position towards the free market can have as antecedents of entrepreneurial intention.